Neurophysiological approaches for managing pain in multiple sclerosis: a mini review - Ayache, Samar S.; Chalah, Moussa A. (Frontiers in Human Neuroscience, 2025)
Chronic pain is a prevalent yet often under-recognized symptom among individuals with multiple sclerosis (MS), affecting 29–86% of the population. This condition can significantly impact the individuals' functionality, including their capacity to engage in professional activities. The pathophysiology underlying this condition remains intricate and not fully elucidated, and inadequate responses to pharmacological interventions or adverse effects can hinder its management. In light of these observations, there is an urgent need to identify new therapeutic interventions. Non-invasive brain stimulation (NIBS) techniques hold promise for addressing MS-related pain. This mini-review aims to analyze the findings from studies using NIBS techniques, such as transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS), to assess their analgesic potential in people with MS. Seven relevant reports are available. Five of these studies used tDCS, one utilized a transcranial random noise stimulation (tDCS variant), and one compared rTMS with transcranial theta burst stimulation (rTMS variant). The results indicate the potential benefits of NIBS for pain management in MS. However, the study's limitations, including the scarcity of data, small sample size, the limited number of sessions, sham design, and brief follow-up, are also noted and discussed. Finally, directions for future research are suggested.